Depth, Highness and DNR degrees - Moser, Philippe; Stephan, Frank (Discrete mathematics and theoretical computer science, 2017)
We study Bennett deep sequences in the context of recursion theory; in particular we investigate the notions of O(1)-deepK, O(1)-deepC , order-deep K and order-deep C sequences. Our main results are that Martin-Loef random sets are not order-deepC , that every many-one degree contains a set which is not O(1)-deepC , that O(1)-deepC sets and order-deepK sets have high or DNR Turing degree and that no K-trival set is O(1)-deepK. Comment: journal version, dmtcs